Martingale methods in financial modelling - Musiela Marek; Rutkowski Marek (Berlin Springer-Verlag, 2005)
In the 2nd edition a brand new chapter is devoted to volatility risk. The theme of stochastic volatility also reappears systematically in the second part of the book. This edition concentrates on the most pertinent and widely accepted modelling approaches
Keywords: Applied statistics; Financial modelling; Martingale methods